Makna Simbolik dalam Iklan Cerdas dan Target Perilaku Khalayak - Ferdinand Eskol Tiar Sirait (PERSPEKTIF, 2021)
This article aims to discuss the concept of smart advertising, especially with regard to the goals and effects of smart smart advertising to form the top of the mind of the audience. This research was conducted with library research (library research) with a descriptive analysis approach, namely collecting data, compiling or clarifying, and interpreting it. The technique used in this research, namely by analyzing advertisement sentences, seen from the use of interference. The data in this study were obtained from several sources in which there was interference. This study concludes that one of the most widely used strategies to increase the value of advertising is "smart advertising" or advertising that is carried out with behavioral targeting. By using information about online behavior, including sites visited and interest in certain types of content, behavior targeting seeks to serve ads that are more attractive to certain groups of consumers. Despite the potential for a dramatic increase for online advertisers and publishers, some users and user advocacy groups have expressed concern over the privacy concerns posed by behavioral targeting